Embedded ash-free coal-based denitration catalyst and preparation method thereof

By embedding metal oxides such as MnO2 and CeO2 into ashless coal, an embedded ashless coal-based denitrification catalyst was prepared, which solved the problem that the active components of the existing denitrification catalyst were prone to fall off, and achieved high pressure resistance, long-lasting activity and excellent low-temperature catalytic performance.

CN119500111APending Publication Date: 2025-02-25XI'AN UNIVERSITY OF ARCHITECTURE AND TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411656099.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-25

Smart Images

  • Figure CN119500111A_ABST
    Figure CN119500111A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of flue gas denitration catalysts, in particular to an embedded ash-free coal-based denitration catalyst and a preparation method thereof. The preparation method of the embedded ashless coal-based denitration catalyst comprises the following steps: preparing ashless coal by adopting a solvothermal extraction method; the method comprises the following steps: uniformly mixing ashless coal with a metal oxide and a binder to obtain a mixture; carrying out cold press molding on the mixture, and drying to obtain a molded body; and performing carbonization and activation treatment on the molded body to obtain the embedded ash-free coal-based denitration catalyst. And the metal oxides are MnO2 and CeO2. The active carbon matrix is embedded in the metal oxide, so that the active components are not easy to fall off in the transportation and use processes, and the service life of the catalyst is prolonged. The ashless coal serves as a carbon matrix, the number of micropores of the catalyst is increased, gas molecules are promoted to be adsorbed on the surface of the catalyst for reaction, and the strength of the catalyst is further enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of flue gas denitration catalysts, and in particular to an embedded ash-free coal-based denitration catalyst and a preparation method thereof. Background Art

[0002] NO x It is one of the main pollutants in the atmosphere, mainly coming from coal-fired power plants, industrial kilns, metallurgy and other industries. x It will cause a series of environmental problems such as acid rain and photochemical smog, and will also damage the human immune system and nervous system. The mainstream denitrification technology today is the selective catalytic reduction method (NH3-SCR), the core of which is the catalyst. x -CeO2 / AC catalyst has excellent denitrification performance due to the good reduction performance of MnO2, the excellent oxygen storage capacity of CeO2 and the huge specific surface area of ​​AC. It is considered to be a promising catalyst for removing nitric oxide from industrial flue gas. The commonly used catalyst preparation method is the impregnation method, which loads the active components on the carrier surface. However, during the transportation and use of the catalyst, the friction caused by the impact of flue gas causes the active components to fall off easily, reducing the catalytic activity. Summary of the invention

[0003] In view of the problem that the active components of the denitration catalyst in the prior art are easy to fall off, the present invention proposes an embedded ashless coal-based denitration catalyst and a preparation method thereof. The embedded ashless coal-based denitration catalyst of the present invention has high compressive strength, and the metal oxide is not easy to fall off, which can ensure long-lasting catalytic activity and catalyst application life, has rich pore structure, and has excellent low-temperature catalytic performance.

[0004] To achieve the above object, the present invention provides the following solutions:

[0005] One of the technical solutions of the present invention is a method for preparing an embedded ashless coal-based denitration catalyst, comprising the following steps:

[0006] Ash-free coal is obtained by solvent thermal extraction;

[0007] The ash-free coal is mixed with the metal oxide and the binder to obtain a mixture;

[0008] cold-pressing the mixture into a molded body, and drying the mixture to obtain a molded body;

[0009] Carrying out carbonization and activation treatment on the molded body to obtain the embedded ash-free coal-based denitration catalyst;

[0010] The metal oxides are MnO2 and CeO2.

[0011] The second technical solution of the present invention is an embedded ash-free coal-based denitrification catalyst prepared by the above-mentioned preparation method.

[0012] The third technical solution of the present invention is the application of the above-mentioned embedded ash-free coal-based denitrification catalyst in low-temperature NH3-SCR denitrification.

[0013] The present invention discloses the following technical effects:

[0014] (1) The raw materials used in the present invention are low in cost, abundant in resources and easily available, harmless to human body and environment, and can be used for nitrogen oxide treatment in steel enterprises, thus belonging to an environmentally friendly catalyst.

[0015] (2) The present invention uses MnO2 and CeO2 as active components, which can combine the multivalent state and excellent low-temperature activity of MnO2 and the good oxygen storage capacity of CeO2 to ensure a stable nitric oxide conversion rate (the conversion rate of NO of the embedded ash-free coal-based denitrification catalyst of the present invention is greater than 70%).

[0016] (3) The metal oxides are embedded in the activated carbon matrix, and the active components are not easy to fall off during transportation and use, thus extending the service life of the catalyst.

[0017] (4) Ash-free coal serves as a carbon matrix, which increases the number of micropores in the catalyst, promotes the adsorption of gas molecules on the catalyst surface and subsequent reaction, and further enhances the catalyst strength. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0019] Figure 1 The NO conversion test results of the catalysts prepared in Example 1, Comparative Example 1 and Comparative Example 2 are shown.

[0020] Figure 2 These are the denitration stability test results of the catalysts prepared in Example 1, Comparative Example 1 and Comparative Example 2.

[0021] Figure 3 N2 adsorption-desorption (a) and pore size distribution diagram (b) of the catalysts prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0022] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0023] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0024] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0025] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0026] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0027] The "room temperature" described in the present invention, unless otherwise specified, refers to 20-30°C.

[0028] In view of the problem that the active components of the denitration catalyst in the prior art are easy to fall off, the present invention adopts the method of mixing, molding, carbonization, and activation to embed the active components in the carbon matrix to avoid their falling off. In view of the fact that the ash in the activated carbon as a catalyst carbon matrix will hinder the formation of micropores and the low catalyst strength, coal contains rich surface functional groups, and the activated carbon made from it can ensure the smooth progress of the catalytic reaction. However, the presence of ash in the coal-based activated carbon matrix will block some pores, and after removing the ash, some new pore structures will be formed, which will promote the adsorption of gas on the catalyst surface and increase the reaction rate. And after deashing, the fixed carbons are more tightly bound, and the bonding between carbon elements can further improve the catalyst strength. However, there is no research on NH3-SCR denitration of carbon-based deashing catalysts.

[0029] The first aspect of the present invention provides a method for preparing an embedded ashless coal-based denitration catalyst, comprising the following steps:

[0030] Ash-free coal is obtained by solvent thermal extraction;

[0031] The ash-free coal is mixed with the metal oxide and the binder to obtain a mixture;

[0032] cold-pressing the mixture into a molded body, and drying the mixture to obtain a molded body;

[0033] Carrying out carbonization and activation treatment on the molded body to obtain the embedded ash-free coal-based denitration catalyst;

[0034] The metal oxides are MnO2 and CeO2.

[0035] In a preferred embodiment of the present invention, the ash-free coal is obtained by adding pulverized lignite into a mixed solution of 1-methylnaphthalene and methanol for extraction.

[0036] In a preferred embodiment of the present invention, the volume ratio of 1-methylnaphthalene to methanol is 500:63; the extraction temperature is 350°C and the time is 1 hour; after the extraction is completed, a drying step at 250°C is also included; the mass ratio of lignite to the extractant (a mixed solution of 1-methylnaphthalene and methanol) is 1:100.

[0037] In a preferred embodiment of the present invention, the mass ratio of MnO2 to CeO2 is (7-8):(3-4).

[0038] In a preferred embodiment of the present invention, the added amount of the metal oxide is 7%-8% of the mass of the ash-free coal.

[0039] In a preferred embodiment of the present invention, the binder is coal tar and water; the mass ratio of the coal tar and water is (4-5):(1-2).

[0040] The present invention does not impose any particular limitation on the amount of the binder used. The amount of the binder used is sufficient to wet and shape the ash-free coal and the metal oxide.

[0041] In a preferred embodiment of the present invention, the particle size of the ash-free coal is not greater than 75 μm.

[0042] In a preferred embodiment of the present invention, the cold press molding pressure is 15-20 MPa and the time is 90 seconds.

[0043] In a preferred embodiment of the present invention, the drying temperature is 105° C. and the drying time is 8 hours. The purpose of drying is to remove excess moisture.

[0044] In a preferred embodiment of the present invention, the carbonization and activation treatment is specifically as follows: in an inert atmosphere, the temperature is raised to 600°C at a rate of 10°C / min for carbonization for 90 minutes; then the temperature is raised to 900°C at a rate of 10°C / min and water vapor is introduced for activation for 30 minutes.

[0045] In some embodiments of the present invention, the carbonization and activation treatments are carried out in a tubular furnace; the amount of water vapor introduced is 1.5 ml / min.

[0046] A second aspect of the present invention provides an embedded ash-free coal-based denitration catalyst prepared by the above-mentioned preparation method.

[0047] A third aspect of the present invention provides an application of the above-mentioned embedded ash-free coal-based denitrification catalyst in low-temperature NH3-SCR denitrification.

[0048] In some embodiments of the present invention, the temperature of the low-temperature NH3-SCR denitrification is 80-220°C.

[0049] In order to prevent the active components on the surface of the denitration catalyst from falling off, the present invention uses a solution thermal extraction method to prepare ash-free coal as a carbon matrix, and then embeds metal oxides into the carbon matrix through the process of mixing, molding, carbonization and activation to prepare a denitration catalyst. MnO2 and CeO2 are selected as active components, combined with the excellent low-temperature catalytic activity of MnO2 and the good oxygen storage capacity of CeO2, to ensure that good low-temperature catalytic activity is maintained during the denitration process. In addition, ash-free coal as a carbon matrix with metal oxides embedded in it can effectively improve the catalyst strength and extend the service life of the catalyst.

[0050] The technical solutions described in the present invention, unless otherwise specified, are all conventional solutions in the art, and the reagents or raw materials used, unless otherwise specified, are purchased from commercial channels or have been disclosed.

[0051] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0052] Example 1

[0053] Measure 500ml of 1-methylnaphthalene with a purity greater than 99.7% and mix it with 63ml of methanol. Crush the lignite to less than 75μm and weigh 55g. Place the weighed raw materials into a high-temperature and high-pressure reactor, heat it to 350℃ and extract it for 1h while stirring. After cooling to room temperature, use a syringe to extract the upper layer of coal slurry and put it into a magnetic boat. Dry it in a drying oven at 250℃ for 2.5h to evaporate the liquid. The powder adhering to the wall of the magnetic boat is ash-free coal. 6-8g of ash-free coal can be obtained each time.

[0054] Take 15 g of ash-free coal, 0.74 g of MnO2, and 0.32 g of CeO2 and mix them evenly. Then add 4.5 g of coal tar and 1.13 ml of deionized water and stir until moist to obtain a mixture.

[0055] Each time, 2±0.1g of the mixture was weighed and filled into a stainless steel briquetting mold with a diameter of 2cm. A vertical hydraulic jack was used to cold press for 90s at a pressure of 20Mpa, and finally kept in a drying oven at 105℃ for 8h to remove excess water to obtain a molded body. It should be noted that after each block making, the mold needs to be wiped and cleaned with anhydrous ethanol to prevent the sample from being too tightly bonded to the mold and causing the molded body to break.

[0056] The formed body was placed in a magnetic boat, and then the magnetic boat was placed in a tubular furnace. 200 ml / min of N2 was introduced as a protective gas, and the temperature was raised to 600°C at a rate of 10°C / min for carbonization for 90 minutes to volatilize some organic matter in the coal to form a pore structure.

[0057] After carbonization, there is no need to remove the sample. The temperature is still raised to 900°C at a rate of 10°C / min, and a steam generator is used to generate steam to activate the sample at a rate of 1.5ml / min for 30min to obtain an embedded ash-free coal-based denitrification catalyst, which is recorded as YN-AFC.

[0058] The denitration performance of the embedded ash-free coal-based denitration catalyst prepared in Example 1 was tested: the simulated reaction gas composition of nitric oxide was nitric oxide (0.06%), ammonia (0.06%), oxygen (11%) and nitrogen as a balance gas, and the total gas flow rate was 180 ml / min. The sample was placed in a continuous flow fixed bed to control the flue gas temperature, the rotor flowmeter controlled the gas flow rate, the gas was mixed in the mixing tank and then passed through the sample, and the gas content at the tail gas was recorded using a flue gas analyzer.

[0059] The calculation formula of nitric oxide removal efficiency is as follows: nitric oxide removal rate = (nitric oxide content in raw gas - nitric oxide content in tail gas) / nitric oxide content in raw gas × 100%.

[0060] Take 1g of the embedded ash-free coal-based denitration catalyst prepared in Example 1 and fill it in a quartz reaction tube, record the denitration activity of the catalyst at 80-220°C, and the nitric oxide conversion rate increases with the increase in temperature. Control the reaction temperature to 180°C, introduce a simulated reaction gas containing nitric oxide, and detect the concentration of nitric oxide in the inlet and outlet gases; the embedded ash-free coal-based denitration catalyst prepared by the above method has a removal rate of 81% for nitric oxide in the simulated reaction gas at 180°C, and the catalytic activity is maintained for 48 hours without decreasing. Use a digital push-pull dynamometer to test the catalyst strength multiple times and obtain an average value of 883N / m 2 .

[0061] Comparative Example 1

[0062] Take 15g of mother coal for making ash-free coal (i.e. lignite crushed to less than 75μm), 0.74g of MnO2, and 0.32g of CeO2 and mix them evenly. Then add 4.5g of coal tar and 1.13ml of deionized water and stir until moist to obtain a mixture.

[0063] Each time, 2±0.1g of the mixture was weighed and filled into a stainless steel briquetting mold with a diameter of 2cm. A vertical hydraulic jack was used to cold press for 90s at a pressure of 20Mpa, and finally kept in a drying oven at 105℃ for 8h to remove excess water to obtain a molded body. It should be noted that after each block making, the mold needs to be wiped and cleaned with anhydrous ethanol to prevent the sample from being too tightly bonded to the mold and causing the molded body to break.

[0064] The formed body was placed in a magnetic boat, and then the magnetic boat was placed in a tubular furnace. 200 ml / min of N2 was introduced as a protective gas, and the temperature was raised to 600°C at a rate of 10°C / min for carbonization for 90 minutes to volatilize some organic matter in the coal to form a pore structure.

[0065] After carbonization, the sample does not need to be taken out, and the temperature is still raised to 900°C at a rate of 10°C / min, and a steam generator is used to generate steam to activate the sample at a rate of 1.5ml / min for 30min, thereby obtaining an embedded denitration catalyst, which is denoted as YN-AC. (The only difference from Example 1 is that the ash-free coal used to prepare the catalyst is replaced with lignite powder with the same particle size as the ash-free coal)

[0066] The denitration performance of the embedded denitration catalyst prepared in Comparative Example 1 was tested in the same manner as in Example 1. The results showed that the conversion rate of the embedded denitration catalyst prepared in Comparative Example 1 to nitric oxide in the simulated reaction gas at 180°C was 70%, and the catalytic activity was maintained for 48 hours without reduction. The catalyst strength was tested multiple times using a digital push-pull dynamometer and the average value was 515 N / m 2 .

[0067] Comparative Example 2

[0068] The manganese-cerium-carbon denitrification catalyst was prepared by impregnation method and compared with the embedded denitrification catalyst. Specifically, 15 g of mother coal for making ash-free coal (i.e. lignite crushed to less than 75 μm) was taken, and then 4.5 g of coal tar and 1.13 ml of deionized water were added and stirred until wet to obtain a mixture.

[0069] Each time, 2±0.1g of the mixture was weighed and filled into a stainless steel briquetting mold with a diameter of 2cm. A vertical hydraulic jack was used to cold press for 90s at a pressure of 20Mpa, and finally kept in a drying oven at 105℃ for 8h to remove excess water to obtain a molded body. It should be noted that after each block making, the mold needs to be wiped and cleaned with anhydrous ethanol to prevent the sample from being too tightly bonded to the mold and causing the molded body to break.

[0070] The formed body was placed in a magnetic boat, and then the magnetic boat was placed in a tubular furnace. 200 ml / min of N2 was introduced as a protective gas, and the temperature was raised to 600°C at a rate of 10°C / min for carbonization for 90 minutes to volatilize some organic matter in the coal to form a pore structure.

[0071] After carbonization, there is no need to remove the sample. The temperature is still raised to 900°C at a rate of 10°C / min, and water vapor is generated by a water vapor generator and passed through the sample at a rate of 1.5 ml / min for 30 minutes to activate the sample to obtain a pure activated carbon catalyst.

[0072] Manganese nitrate and cerium nitrate with a purity greater than 99.7% were selected, the mass fraction of manganese nitrate and cerium nitrate was 7% of the mass of coal powder (mother coal of ash-free coal), the mass ratio of manganese nitrate and cerium nitrate was 7:3, and deionized water was added as a precursor solution. The prepared pure activated carbon catalyst was immersed in the precursor solution, immersed at room temperature for 1 hour, and then placed in a 60°C water bath for ultrasonic impregnation until the excess water evaporated. The sample was dried in a drying oven at 105°C for 8 hours, and finally calcined in a protective N2 atmosphere at 400°C for 4 hours to obtain a manganese-cerium carbon denitration catalyst prepared by impregnation method, recorded as YN-ACI.

[0073] The denitration performance of the denitration catalyst obtained in Comparative Example 2 was tested in the same manner as in Example 1. The results showed that the conversion rate of the denitration catalyst prepared by the impregnation method in Comparative Example 2 to nitric oxide in the simulated reaction gas at 180°C was 78%, and the nitric oxide conversion rate showed a slow downward trend as time went on. The catalyst strength was tested multiple times using a digital push-pull dynamometer and the average value was 507N / m 2 .

[0074] The strengths of the catalysts prepared in Example 1 and Comparative Examples 1-2 are statistically shown in Table 1.

[0075] Table 1 Catalyst strength

[0076]

[0077] In practical applications, the powder generated by the catalyst fragmentation fills the stacking gap, which will hinder the circulation of flue gas and reduce the denitrification efficiency. It will also cause a violent collision between the catalyst and the flue gas, resulting in the shedding of active components and shortening the service life. Therefore, good strength is a major physical property of the catalyst. In Table 1, it can be found that the strength of Example 1 is greatly improved compared with Comparative Example 1. This is because the carbon atoms in the coal are more tightly bound after deashing. It can be seen that the method of the present invention can effectively inhibit the fragmentation of the catalyst during use.

[0078] exist Figure 1 In the experiment, the NH3-SCR denitration activities of Example 1, Comparative Example 1 and Comparative Example 2 were further compared. It can be found that compared with Comparative Example 1, the denitration activity of Example 1 is higher as a whole, reaching a maximum of 75%. The activity of Comparative Example 2 is not much different from that of Example 1. It is proved that the embedded ash-free coal-based denitration catalyst in the present invention can ensure the nitrogen monoxide conversion rate on the basis of improving the strength.

[0079] exist Figure 2 It can be found that at 180°C, the denitration activity of Example 1 is stable, while the conversion rate of nitrogen monoxide in Comparative Example 2 shows a slight downward trend as the test time increases. This indicates that the embedded ash-free coal-based catalyst in the present invention can slow down the shedding of metal oxides on the sample surface and ensure the denitration reaction for a long time.

[0080] exist Figure 3 In the figure, (a) is the adsorption-desorption curve. It can be observed that the adsorption curve of all catalysts rises rapidly when the relative pressure P / P0<0.1, which proves the existence of a large number of micropores. The N2 adsorption of comparative example 1 is significantly less than that of other catalysts, and the hysteresis loop is narrower and longer, indicating that its physical adsorption performance is the weakest. However, after deashing, the N2 adsorption of the YN-AFC catalyst is significantly improved. (b) is a mesopore distribution diagram. Deashing the catalyst can effectively increase the specific surface area, which is conducive to the formation of mesopores. This may be due to the lack of ash obstruction, which helps the small molecules of coal to overflow.

[0081] In summary, the present invention prepares an embedded ashless coal-based denitration catalyst based on the catalytic reduction of nitrogen monoxide. It is safe to operate and easy to implement. The active components are tightly embedded in the carbon matrix to ensure the service life of the catalyst. In addition, the mechanical strength of the catalyst is significantly enhanced, and it is prevented from breaking while ensuring the activity. It is beneficial to remove nitrogen monoxide from flue gas.

[0082] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing an embedded ashless coal-based denitration catalyst, characterized in that: The following steps are involved: Ash-free coal is obtained by solvent thermal extraction; The ash-free coal is mixed with the metal oxide and the binder to obtain a mixture; cold-pressing the mixture into a molded body, and drying the mixture to obtain a molded body; Carrying out carbonization and activation treatment on the molded body to obtain the embedded ash-free coal-based denitration catalyst; The metal oxides are MnO2 and CeO2.

2. The method for preparing an embedded ash-free coal-based denitration catalyst according to claim 1, characterized in that: The mass ratio of MnO2 and CeO2 is (7-8):(3-4).

3. The method for preparing an embedded ash-free coal-based denitration catalyst according to claim 1, characterized in that: The added amount of the metal oxide is 7%-8% of the mass of the ash-free coal.

4. The method for preparing an embedded ash-free coal-based denitration catalyst according to claim 1, characterized in that: The binder is coal tar and water; the mass ratio of the coal tar and water is (4-5):(1-2).

5. The method for preparing an embedded ash-free coal-based denitration catalyst according to claim 1, characterized in that: The particle size of the ash-free coal is not greater than 75 μm.

6. The method for preparing an embedded ash-free coal-based denitration catalyst according to claim 1, characterized in that: The cold pressing process is performed at a pressure of 15-20 MPa and a time of 90 seconds.

7. The method for preparing an embedded ash-free coal-based denitration catalyst according to claim 1, characterized in that: The carbonization and activation treatment is specifically as follows: in an inert atmosphere, the temperature is raised to 600° C. at a rate of 10° C. / min for carbonization for 90 minutes; then the temperature is raised to 900° C. at a rate of 10° C. / min and water vapor is introduced for activation for 30 minutes.

8. The method for preparing an embedded ash-free coal-based denitration catalyst according to claim 1, characterized in that: The ash-free coal is obtained by adding pulverized lignite into a mixed solution of 1-methylnaphthalene and methanol for extraction.

9. An embedded ash-free coal-based denitration catalyst prepared according to the preparation method according to any one of claims 1 to 8.

10. Use of the embedded ash-free coal-based denitration catalyst according to claim 9 in low-temperature NH3-SCR denitration.